Association of Maternal Age to Development and Progression of Retinopathy of Prematurity in Infants of Gestational Age under 33 Weeks - Atsuro Uchida; Masayuki Miwa; Hajime Shinoda; Takashi Koto; Norihiro Nagai; Hiroshi Mochimaru; Yohei Tomita; Mariko Sasaki; Kazushige Ikeda; Kazuo Tsubota; Yoko Ozawa (Journal of Ophthalmology)
Aim. To find predictive and indicative markers of risk for development of retinopathy of prematurity (ROP) and its progression to the stage requiring laser treatment, in premature infants whose gestational age (GA) was under 33 weeks. Methods. We retrospectively reviewed medical records of 197 premature infants born in 2005–2010 whose GA<33 weeks and underwent eye screening at Keio University Hospital. The association between candidate risk factors and development or progression of ROP was assessed. Results. Among the 182 eligible infants (median GA, 29.1 weeks; median birth weight (BW), 1028 g), 84 (46%) developed any stage of ROP, of which 45 (25%) required laser treatment. Multivariate analysis using a stepwise method showed that GA (P=0.002; 95% confidence interval (CI), 0.508–0.858), BW (P<0.001; 95% CI, 0.994–0.998), and lower maternal age (P=0.032; 95% CI, 0.819–0.991) were the risk factors for ROP development and GA (P<0.001; 95% CI, 0.387–0.609) and lower maternal age (P=0.012; 95% CI, 0.795–0.973) were for laser treatment. The odds ratio of requiring laser treatment was 3.3 when the maternal age was <33 years. Conclusion. ROP was more likely to be developed and progressed in infants born from younger mother and low GA.